Sliding Modes Strategy Implementation for Controlling Nutrition in Hydroponics Based IoT - Septian Enggar Sukmana; Nurul Anisa Sri Winarsih; Akmaludin Akbar (Journal of Applied Intelligent System, 2019)
To reduce unconsistenly of nutrition sensor data, an analysis which consists of mathemathical model and new control technique is required. In this paper, a simulation of smart garden is performed to simulate a smart green campus. However, the problem appears in this activity, the data form sensor is not consistent and it may harm the plant because sometime the plant may get a much nutrition and another time the plant will get less nutrition. Our propose is on the sensor circuit, we use additional circuit to our TDS meter so the data is normalized using this circuit.